Inversed-planned Respiratory Phase Gating in Lung Conformal Radiotherapy - Modiri, Arezoo (Int J Radiat Oncol Biol Phys, 2017)
BACKGROUND AND PURPOSE: Respiratory gating is a frequently-used clinical motion-management strategy in lung radiotherapy. In conventional gating, the beam is turned on during a pre-determined window; typically, around end-exhalation (EE). In this work, we postulate that the optimal gating window for each beam will be dependent on a variety of patient-specific factors, such as tumor size and location, and the extent of relative tumor and organ motion. MATERIAL AND METHODS: In order to create optimal gating treatment plans, we started from an optimized clinical plan, created a plan per respiratory phase using the same beam arrangements, and used an inverse planning optimization approach to determine the optimal gating window for each beam and optimal beam weights, i.e., monitor units (MUs). Two pieces of information were used for optimization: (i) the state of the anatomy at each phase, extracted from 4D CT scans, and (ii) the time spent in each state, estimated from a 2-minute monitoring of the patient’s breathing motion. We retrospectively studied 15 lung cancer patients clinically treated by hypofractionated conformal radiation therapy, where 45 – 60 Gy was administered over 3 – 15 fractions using 7 – 13 beams. Mean gross tumor volume and respiratory-induced tumor motion was 82.5 cc and 1.0 cm, respectively. RESULTS: Although patients spent most of their respiratory cycle in EE, our optimal gating plans used EE for only 34% of the beams. Using optimal gating, maximum and mean doses to esophagus, heart and spinal cord were reduced by an average of 15 – 26% and the beam-on times were reduced by an average of 23% compared to equivalent single-phase EE gated plans (p < 0.034, paired, two – tailed T – test). CONCLUSIONS: We introduce a personalized respiratory-gating technique where inverse planning optimization is used to determine patient- and beam-specific gating phases towards enhancing dosimetric quality of radiotherapy treatment plans.